Readiness to deliver quality curative care for under-five children at health posts in Ethiopia - Dawit Wolde Daka; Muluemebet Abera Wordofa; Mirkuzie Woldie (BMC Health Services Research)
Abstract Background The institutionalization of village health services with salaried community health workers has been established in Ethiopia for over a decade. However, there are serious concerns about the capacity of health posts to provide quality curative care for children under-five.Understanding the readiness of health posts is crucial for improving the care given to sick children. Therefore, this study aimed to assess the readiness of health posts to deliver quality curative care for children under-five in four regional states in Ethiopia. Methods A facility-based cross-sectional study was conducted at selected health posts across 10 zones in the Amhara, Oromia, SNNP, and Tigray regions. Study participants, including health posts and health extension workers, were selected using a two-stage stratified cluster sampling strategy. The readiness of health post was assessed in terms of infrastructure, human resources, medicines, medical equipment and supplies and job aids. The variations in health post readiness were analyzed using a One-way analysis of variance (ANOVA). Results A survey was conducted on 169 health posts and 276 health extension workers. The majority of health posts had a toilet facility (83%) and water supply (62%). However, less than a quarter had electricity connection (22%) and communication equipment (18%). Over three-fourths of health extension workers were trained (83%) and supervised (78%) on clinical management of sick children. Less than half (44%) had received clinical mentorship. Availability of essential medicines ranged from 81% for zinc tablets to 28% for cotrimoxazole. Similarly, availability of essential medical equipment varied from 57% for blood pressure apparatus to 86% for thermometer and 99% for Mid-Upper Arm Circumference tape. Only a small portion of health posts (8%) had all critical items for infection prevention practices, which are essential for quality care. Overall, the average percentage availability of items to provide quality curative care to children was 66%, with health post preparedness significantly varying across regions (P < 0.0001). Conclusions The readiness for delivering quality curative care was below standard and significantly varied among health posts across regions. Serious attention is needed to ensure the sustained availability of critical inputs such as trained health extension workers, medicines, medical equipment, and supplies, which is paramount for delivering quality care.